1987
DOI: 10.1007/bf02537297
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics of and discrimination between dietaryRRR‐ andSRR‐α‐tocopherols in the male rat

Abstract: The net rates of uptake of the natural (2R,4'R,8'R) diastereoisomer of alpha-tocopherol (alpha-T) and the biodiscrimination relative to its 2S-epimer (2S,4'R,8'R) have been measured, in two experiments, for the blood and 21 tissues of male Sprague-Dawley rats fed over a period of several months diets containing deuterium-substituted forms of the alpha-T acetates. Gas chromatography-mass spectrometry was used to measure the amount of deuterated tocopherols taken up relative to the amount of nondeuterated tocoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
2
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(106 citation statements)
references
References 36 publications
10
91
2
3
Order By: Relevance
“…Interestingly, the immunosuppressive effect of CsA was not altered by WGO. Previously, it has been reported that synthetic vitamin E does not have the same biological activity of natural vitamin E (Ingold et al, 1987;Pfluger et al, 2004). The richest known natural dietary source of vitamin E is WGO (Shurpalekar & Rao, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the immunosuppressive effect of CsA was not altered by WGO. Previously, it has been reported that synthetic vitamin E does not have the same biological activity of natural vitamin E (Ingold et al, 1987;Pfluger et al, 2004). The richest known natural dietary source of vitamin E is WGO (Shurpalekar & Rao, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In humans (61)(62)(63), monkeys (64) and rats (65), RRRa-tocopherol is preferentially transported in plasma. Studies using perfused monkey livers demonstrated that RRR-atocopherol is preferentially secreted in nascent VLDL (54).…”
Section: Discussionmentioning
confidence: 99%
“…A cytosolic a-tocopherol-binding protein, also able to interact with other tocopherols, of apparent molecular mass 30.5 kDa, has been isolated from rat liver [20, 211. In mammals, a-tocopherol is secreted from liver associated with nascent very-low-density lipoproteins [23] and is carried in blood primarily by low-density and high-density lipoproteins [23,241. Experiments on a-tocopherol stereoisomer kinetics and uptake in different tissues revealed differences, with an especially high discrimination in gut and in brain [25].…”
mentioning
confidence: 99%